Inovasi Produk Minuman Bunga Telang Beras Dan Kencur Bersama Masyarakat Dusun Potrojalu Karanganyar - Meliana Novitasari; Rina Tri Handayani; Ahmad Syauqi Mubarak; Muna Bekti Sayekti (Pakis Journal Institute, 2024)
Herbal drinks are drinks made from natural ingredients or plants and are used for health. One of the herbal drink innovations is the herbal drink of butterfly pea flowers, rice, and galangal, abbreviated as Langbecur. These three natural ingredients have health-improving benefits because they contain many compounds that are beneficial for the body. This community service activity aims to provide information to the people of Potrojalu Hamlet about the benefits of butterfly pea flowers, rice, and galangal. In addition, it also motivates the community so that they can use these ingredients to be processed into herbal drinks to improve the family economy. The method of this activity has several stages, namely the survey stage, the socialization and implementation stage, and the evaluation stage. The evaluation stage used in this activity is a questionnaire. The questionnaire was distributed to residents who were present to assess their level of understanding of the material that had been given. The results of the questionnaire showed that 81% (30 people) of participants understood the material presented, 11% (4 people) did not understand, and 8% (3 people) did not understand. After the delivery of the material was completed, the team also distributed samples of langbecur drinks to people who could not attend. This activity received a good response from the community. Residents hope that activities like this can take place regularly. Keywords: Butterfly Pea Flowers, Galangal, Herbal Drinks, Potrojalu Hamlet, Rice.